2019
DOI: 10.1089/mdr.2018.0278
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Carbapenem-Resistant Gram-Negative Bacilli Pathogens from Hospitals in Ghana

Abstract: Phenotypic and genotypic characterization of carbapenem-resistant gram-negative bacilli pathogens from hospitals in Ghana. Microbial drug resist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 34 publications
18
46
2
Order By: Relevance
“…In addition, we found one carbapenem-resistant Pseudomonas aeruginosa. Carbapenem-resistance is still comparatively rare in Ghana: 2.9% in Gram-negative rodshaped bacteria, predominantly in Pseudomonas aeruginosa and Acinetobacter baumannii [25]. In summary, the observed resistance patterns make any rational antimicrobial therapy challenging, indicating a need for routine diagnostics including antibiotic susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found one carbapenem-resistant Pseudomonas aeruginosa. Carbapenem-resistance is still comparatively rare in Ghana: 2.9% in Gram-negative rodshaped bacteria, predominantly in Pseudomonas aeruginosa and Acinetobacter baumannii [25]. In summary, the observed resistance patterns make any rational antimicrobial therapy challenging, indicating a need for routine diagnostics including antibiotic susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, a recent study involving 111 carbapenem-resistant Gram-negative bacteria showed that none of the isolates harbored KPC genes. However, the carbapenemase genes identified were blaNDM-1, blaVIM-1 and blaOXA-48 in A. baumannii, Pseudomonas species, and K. pneumoniae, respectively [78] . In Uganda, a study by Okoche et al [80] found carbapenemase prevalence of 22.4% and 28.6% using phenotypic and genotypic tests.…”
Section: Acquisition Of Multidrug-resistant Organismsmentioning
confidence: 97%
“…In West Africa, Nigeria and Ghana are the leading countries in the region that have documented data regarding CRE [77] . In Nigeria, a study reported carbapenemase prevalence of 33.5% in a hospital setting [6] , and Codjoe [78] reported 12.5% and 15.4% carbapenemase production in E. coli and K. pneumoniae isolates. Ogbolu and Webber [79] identified blaNDM, blaVIM, and blaGES among P. aeruginosa, Proteus spp., K. pneumoniae and E. coli, respectively as the genes responsible for resistance in β-lactam antibiotics in Nigeria.…”
Section: Acquisition Of Multidrug-resistant Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative Bacilli (GNB) are implicated in a wide range of diseases, such as pneumonia, meningitis, septicemia, and urinary tract infections [1]. According to China Antimicrobial Resistance Surveillance System (CARSS) monitoring data (http://www.carss.cn/), GNB have been shown to account for 70.6% of the total number of bacteria in hospitals, which are resistant to most available antibiotics and have developed built-in abilities to acquire new ways of resistance [2].…”
Section: Introductionmentioning
confidence: 99%